Le rôle du livre imprimé dans la formation et le développement de la littérature en grec vulgaire (XVIe-XVIIe siècles) - Michel Lassithiotakis (Revue des Mondes Musulmans et de la Méditerranée)
This article, attempts to examine various problems which are linked with the history of the Greek printed book from 1509 (editio princeps of the Apokopos of Bergadis, the first modern Greek work to appear in print) to 1713 (first edition of the Erotokritos of Kornaros). It seeks to show that, during these two centuries, the printing industry was an organic and creative element in the intellectual and literary life of the Latin occupied Greek Levant and that printing influenced not only the reception but also the development of early modern Greek literature.